Public financial management systems Vietnam key elements from a financial management perspective. (Metro Manila, Philippines Asian Development Bank, 2017)
It also provides insights into the quality of the country internal control systems, staffing resource capacity, and information technology structure. The publication aims to enhance the understanding of project teams and consultants on public financial management systems with the objective of improving the quality of financial management assessments during project preparation. High-quality financial management assessments support project implementation through the identification and mitigation of key fiduciary risks and the implementation of appropriate mitigating actions and reforms.
Keywords: Public administration -- Developing countries; Industrial policy -- Pacific Area; Electronic books